The Gait of BTKLPP Ambon in Efforts to Eliminate Filariasis in Eastern Indonesia - Tulak, Zusana Lena (Miracle Journal of Public Health, 2022)
Filariasis is one of tropical diseases that can lead to permanent disabilities and social stigma in society. Indonesia has chronic cases up to 9354 people by 2021, and Papua is the province with the most chronic cases, namely 3629. This paper aims to expand the work of BTKLPP Ambon to describe his efforts to eliminate filariasis in eastern Indonesia. The elimination effort took the form of a survey to assess the prevalence of microfilariasis conducted in Maluku Province, West Papua and Papua. The population was 1,413,367 individuals, while the sample studied was 4,999. This survey was conducted using 2 methods, namely Finger Blood Test and Rapid Test (FTS). The results are a step for the districts/cities to eliminate filariasis: Central Maluku District, West Seram District, Tual City and Southwest Maluku District passed the Pre TAS (mf rate 0%); South Sorong Regency passed the mid-term poll (Mf rate 1.6%); Jayapura City failed Pre TAS (mf rate 4.8%), Yapen Islands District passed Pre TAS (mf rate 0.98); Mamberamo District failed the pre-TAS (MF rate 6.1% in sentinel village and 6.7% in spot-check village). The conclusion is that BTKLPP Ambon participated in efforts to eliminate filariasis in Maluku Province, West Papua, and Papua.